Online Monitoring of Geological Methane Storage and Leakage Based on Wireless Sensor Networks - Jeyakkannan1, N.; Nagaraj2, B. (Asian Journal of Chemistry, 2014)
Geological methane monitoring is an important aspect of mining and other petrochemical industries. In hazardous environments local cabling and wiring for the sensors requires frequent maintenance and preventive installations. Proposed work is developed to monitor the concentration of methane using wireless sensor networks linked to Raspberry Pi. A series of methane sensors were developed for monitoring and transmitting the methane concentration. The collected data was transmitted to the base station connected to receiver GPRS connected to Raspberry Pi. Raspberry Pi connected via USB cable to the base computer was used for the data acquisition from various sensors installed on the site. The results obtained from the wireless sensors were compared to that of the acquired signals from the wireless sensor networks. The results obtained were accurate and leakage of methane gas was detected and acquired online using the Raspberry Pi.